THE EFFECTIVENNESS OF SIMON SAYS GAME IN TEACHING VOCABULARY TO THE SECOND YEAR STUDENTS OF SMP NEGERI 1 PALOPO - Felogau, Felogau (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
The objectives of this research were: (1) To find out whether the use of simon says game effective or not to improve the studentsâ vocabulary at the second year of SMP Negeri 1 Palopo and (2) What are the studentsâ responses in learning vocabulary by using simon says game. This research employed pre experimental design. The population of this research was the second year students of SMP Negeri 1 Palopo, which consisting of eight classes in 2016/2017 academic year. The total number of population was 290 students. This research used purposive sampling technique. The sample of this research was one class as an pre experimental class. The sample of the class was 20 students. The research data was collected by using vocabulary test to get the studentsâ vocabulary achievement, which was analyzed by inferential statistic through SPSS version 20.0 for windows program. The studentsâ result of posttest of pre experimental class is significantly improved than the studentsâ result of pretest by the mean score 68.00 > 50.10. The difference of both scores is statistically significant based on the t-test value at significant level 0.05 in which the probability value is lower than the significant level (0.00 < 0.05). So, H1 was accepted and H0 was rejected. It can be concluded that the use of Simon says game effective to improve the studentsâ vocabulary and the students also gave positive responses in learning vocabulary by using Simon says game.